Boolean Algebra

1. May 1, 2016

Kernul

1. The problem statement, all variables and given/known data
Simplify the expression $cb' + ca'b + cabd + cad'$

2. Relevant equations
All the properties of boolean algebra.

3. The attempt at a solution
Here's how I did it:
$$cb' + ca'b + cabd + cad' =$$
$$c(b' + a'b + abd + ad') =$$
$$c(b' + a'b + a(bd + d')) =$$
$$c((a + a')b' + a'b + a(bd + (b + b')d')) =$$
$$c(ab' + a'b' + a'b + a(bd + bd' + b'd')) =$$
$$c(a(b' + bd + bd' + b'd') + a'b' + a'b) =$$
$$c(a(b'(d + d') + bd + bd' + b'd') + a'b' + a'b) =$$
$$c(a(b'd + bd' + bd + bd' + b'd') + a'b' + a'b) =$$
$$c(a(b'd + bd' + bd + b'd') + a'b' + a'b) =$$
$$c(a(b'(d + d') + bd' + bd) + a'b' + a'b) =$$
$$c(a(b'(d + d') + b(d' + d)) + a'b' + a'b) =$$
$$c(a(b' + b) + a'b' + a'b) =$$
$$c(a + a'b' + a'b) =$$
$$c(a + a'(b' + b)) =$$
$$c(a + a') =$$
$$c$$
Is all this correct? Was there a better and faster way to do it?

2. May 1, 2016

Staff: Mentor

Have you checked your answer using a Karnaugh Map? That's a good way for you to check your answers in Boolean algebra manipulations.

(Hint -- I think you'll like what you find in your K-map)

3. May 3, 2016

ehild

It looks correct. Remember the identity A+A'B=A+B. It is very useful!